Enhancing Digital Literacy: An Analysis of Islamic Primary School Prospective Teachers' Competency in Navigating the Digital Era - Maya Agustina; Rina Rahmi; Aidil Saputra (Universitas Pendidikan Ganesha, 2024)
The big data era demands an enhancement in human resource quality, particularly in mastering digital skills, including digital literacy. As part of the younger generation, university students must possess adequate digital literacy to support their academic and professional activities. This study aims to analyze the digital literacy proficiency of students in the Islamic Primary School Teacher Education (PGMI) program using a quantitative approach through a survey method. The study population consisted of 801 students, with a sample of 209 students selected using the stratified random sampling technique. The research instrument was a questionnaire with a Likert scale covering indicators of Digital Skills, Digital Culture, Digital Safety, and Digital Ethics. The findings indicate that the digital literacy proficiency of PGMI students falls within the